Incorporation of Hamstring Grafts Within the Tibial Tunnel After Anterior Cruciate Ligament Reconstruction: Magnetic Resonance Imaging of Suspensory Fixation Versus Interference Screws. (November 2016) - Colombet, Philippe; Graveleau, Nicolas; Jambou, Stephane
Background: The success of anterior cruciate ligament (ACL) reconstruction requires solid graft incorporation within the tunnels to enable graft remodeling. Resorbable interference screws (RIS) provide limited tendon-bone contact because much of the tunnel circumference is occupied by the screw itself, while adjustable suspensory fixation (ASF) systems provide larger contact zones, which favor ligamentization. Purpose: To evaluate ligamentization of a 4-strand semitendinosus (4ST) graft fixed with ASF compared with RIS within the tibial bone tunnel at 6 months postoperatively using magnetic resonance imaging (MRI). Study Design: Cohort study; Level of evidence, 2. Methods: We prospectively enrolled 121 consecutive patients undergoing primary ACL reconstruction using a single-bundle 4ST graft. The femoral end of the graft was fixed using suspensory fixation in all knees. The tibial end of the graft was fixed using ASF in 67 knees and RIS in 54 knees. Six months postoperatively, knee laxity measurements were taken, and MRI was performed to assess graft incorporation within the tibial tunnel. Results: At 6-month follow-up, MRI scans of 109 knees were available for analysis. The mean tibial tunnel enlargement in the ASF group was 2.3 ± 1.1 mm (range, 0.5-6.0 mm), while in the RIS group, it was 4.7 ± 2.8 mm (range, 0.5-19.0 mm) ( P < .001). The Howell graft signal assessment findings were excellent in 97% of knees in the ASF group and in 25% of knees in the RIS group ( P < .001). The mean signal-to-noise quotient (SNQ) was 0.078 ± 0.62 in the ASF group and 0.671 ± 0.83 in the RIS group ( P < .001). Conclusion: ASF provides more favorable conditions than RIS for the incorporation and ligamentization of 4ST grafts within the tibial tunnel. The ASF system used showed very little tunnel widening, which suggests that it grants stabilization. The SNQ was also considerably better in the ASF group.